(untitled) - Poulin, John E (Itasca, Ill., 2000)
Includes bibliographical references and indexes; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Social service -- Methodology; Social group work; Dịch vụ xã hội -- Phương pháp; Công tác xã hội nhóm